ANALISIS KEBUTUHAN PETUGAS PENDAFTARAN PASIEN BERDASARKAN METODE WORKLOAD INDICATOR STAFF NEED (WISN) DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Pri Agung Danarahmanto (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
RSI Sultan Agung Semarang has 12 registration officer. The purpose of this research is to know the needs of registration officers on WISN method in RSI Sultan Agung Semarang in 2016. This research is descriptive research with cross sectional time approaches. Sampling techniques are used accidental sampling techniques. A method of the data used in this research are observation and interview. Based on observation we can conclude that registration for new patient that outpatient needs 7 minutes, while registration for old patient that outpatient needs 3 minutes, registration for patient that use insurance needs 3 minutes, registration patient by phone needs 3 minutes, and  admission patient needs 12 minutes. Based on the calculation with WISN formula, in order to make a better service we need to add one more registration officer